Empat Wajah Topeng Indonesia: Karakteristik Tradisi Pada Budaya Jakarta, Cirebon, Malang, dan Bali - Wiradharma, Gunawan; Soewardjo, B. Kristiono; Sediyaningsih, Sri; Rachman, Ace Sriati; Sopandi, Agus Tatang (Jurnal Sastra Indonesia, 2021)
Indonesian as a country rich in cultural values has a myriad of unique and distinctive traditional cultural arts relics in each region. Art, whatever form it takes, can be a place to accommodate all the aspirations of its people. So that art itself is not only considered a form of “beauty”, but also a representation of the characteristics of a society in question. With the variety of arts in Indonesian, this research focuses on mask arts, especially in performing arts and mask carving art. The interesting thing about the art of this mask is only seen when there is a connection between the masks on the island of Java, especially the Malang, Cirebon, and Jakarta areas with masks in Bali. Therefore, through research with a qualitative descriptive approach has identified the characteristics of tradition in mask art in Bali, Cirebon, Jakarta, and Malang. It is called mask art because there are characters and stories in these masks. This study received a discussion about the position of the four mask-producing areas as an effort to document the oral traditions that developed in the area concerned. This research ultimately resulted in the result that there is homologism and coherence of structures between the masks in Bali, Malang, Cirebon, and Jakarta, both in term of the historical spread of the mask itself, the color symbols used, musical instruments played, the stories of the shows raised, to the characteristics of the mask carving itself.